Mortality and risk factors of vaccinated and unvaccinated frail patients with COVID-19 treated with anti-SARS-CoV-2 monoclonal antibodies: A real-world study. (June 2023) - Nevola, Riccardo; Feola, Giovanni; Ruocco, Rachele; Russo, Antonio; Villani, Angela; Fusco, Raffaele; De Pascalis, Stefania; Core, Micol Del; Cirigliano, Giovanna; Pisaturo, Mariantonietta; Loffredo, Giuseppe; Rinaldi, Luca; et al.
Highlights: Treatment with different monoclonal antibodies (mAbs) has similar effects on frail patients with COVID-19. Anti-COVID-19 vaccination does not impact mortality in patients treated with mAbs. Early administration of mAbs improves outcomes. Early administration of corticosteroids worsens the prognosis. mAb failure predictors are age, hematologic malignancies, and renal insufficiency. Abstract: Objectives: There is a scarcity of data on the outcomes and predictors of therapeutic failure of monoclonal antibodies (mAbs) in frail patients with COVID-19. Methods: Prospective study including consecutive COVID-19 outpatients referred by primary care physicians for mAb treatment. The outcomes evaluated were 60-day mortality, time to SARS-CoV-2 clearance, need for hospitalization, and O2 therapy. Results: Among 1026 COVID-19 patients enrolled, 60.2% received casirivamab/imdevimab and 39.8% sotrivimab. Median age was 63 years, 52.4% were males and median time from positive nasopharyngeal swab to mAbs administration was 3 days (interquartile range, 2-5). 78.1% were vaccinated. Overall, the 60-day mortality was 2.14%. No differences in outcomes were observed between the two mAbs used. No difference was observed in mortality between vaccinated and unvaccinated patients ( P = 0.925); although, lower rate of hospitalization ( P <0.005), less need for O2 therapy ( P <0.0001) and reduced nasopharyngeal swab negativity time ( P <0.0001) were observed in vaccinated patients. Early administration of mAbs was associated with lower mortality ( P <0.007), whereas corticosteroid use worsened prognosis ( P <0.004). The independent predictors associated with higher mortality were older age ( P <0.0001), presence of active hematologic malignancies ( P <0.0001), renal failure ( P <0.041), and need for O2 therapy ( P <0.001). Conclusion: This study shows similar effectiveness among mAbs used, regardless of vaccination status and identifies patients with COVID-19 in whom mAbs have poor activity. Graphical abstract: Image, graphical abstract